Gestão do clima organizacional como ferramenta de satisfação do ambiente corporativo - BARCACAROLI, kamila Borges (109, 2024)
O presente trabalho de pesquisa tem como principal fundamento a importância do clima organizacional dentro do ambiente de trabalho. Para isso, serão descritos os elementos da cultura organizacional, as características do clima organizacional e coletados dados de colaboradores que atuam no setor de telemarketing, visando analisar a correlação entre um ambiente organizacional satisfatório e os resultados qualitativos obtidos pela empresa. A metodologia envolve uma pesquisa qualitativa de caráter descritivo, com base em revisão bibliográfica de artigos, livros e publicações científicas, além de uma pesquisa de campo aplicada a funcionários da área de atendimento ao cliente. O estudo busca, ao final, propor melhorias no clima organizacional para aumentar a satisfação dos colaboradores e contribuir para o desenvolvimento das empresas.

This study aims to investigate the characteristics of organizational climate and its influence on employee satisfaction. The focus of the research is to understand how the absence of an adequate organizational climate negatively impacts both employees and companies, leading to issues such as decreased productivity and high costs related to hiring and training. To achieve this, the study will describe the elements of organizational culture, the characteristics of organizational climate, and collect data from employees working in the telemarketing sector, with the goal of analyzing the correlation between a positive organizational environment and the results achieved by the company. The methodology involves a qualitative, descriptive research approach, based on a literature review of articles, books, and scientific publications, along with a field study applied to customer service employees. The study ultimately aims to propose improvements to the organizational climate to enhance employee satisfaction and contribute to the development of telemarketing companies.
Organizational climate management as a tool for satisfying the corporate environment
Keywords: Satisfação; Satisfação do consumidor; Satisfação no trabalho; Gestão e Negócios